A processing method for medical titanium alloy coronary artery drug-coated stent

By adopting TIMN medical titanium alloy materials and advanced processing technology, to prepare titanium alloy coronary arterial drug coating brackets, solve the problem of risk of ionic ionic ionic ionic in existing materials, and achieve high biocompatibility and erosion resistance. And meet the mechanical performance requirements of the bracket.

CN115069957BActive Publication Date: 2025-01-24GENERAL HOSPITAL OF THE NORTHERN WAR ZONE OF THE CHINESE PEOPLES LIBERATION ARMY +2

Patent Information

Application Number
CN202210717108.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-23
Publication Date
2025-01-24
Estimated Expiration
2042-06-23

AI Technical Summary

Technical Problem

Existing coronary stent materials contain Cr and Ni elements, which have the risk of ion precipitation of harmful elements, affecting biocompatibility and corrosion resistance.

Method used

The TIMN medical titanium alloy material is used to prepare titanium alloy rods and capillary titters and capillary through the vacuum self -consuming electric arc furnace melting, forging, hot rolling, and mechanical perforation. Titanium alloy coronary arterial drug coating bracket.

Benefits of technology

Effectively eliminate the risk of harmful elements, improve the biocompatibility and erosion resistance of the material, meet the mechanical performance requirements of the coronary arterial stent, and realize the uniform distribution of the drug coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115069957B_ABST
    Figure CN115069957B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of cardiovascular stent processing technology, and relates to a processing method for a medical titanium alloy coronary artery drug-coated stent. The chemical composition and mass percentage of the titanium alloy are: Mn 5.0% to 14.0%, Fe≤0.30%, O≤0.16%, N≤0.01%, H≤0.001%, and the remainder is Ti. The present invention adopts a vacuum consumable arc furnace to melt the alloy ingot, and after forging and hot rolling, a titanium alloy rod is obtained, and then mechanical perforation, peeling, centerless grinding, cold rolling, cold drawing and straightening are performed to obtain a finished titanium alloy capillary, and a metal stent is prepared by microsecond fiber laser engraving, vacuum heat treatment and electrochemical polishing. Subsequently, a drug solution is sprayed on the outer surface of the metal stent using a sprayer, and dried in a clean environment, thereby preparing a titanium alloy coronary artery drug-coated stent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cardiovascular stent processing, and in particular relates to a processing method of a medical titanium alloy coronary artery drug-coated stent, and is particularly suitable for a TiMn alloy coronary artery drug-coated stent. Background Art

[0002] At present, coronary stents are usually made of 316L stainless steel (nominal composition: 00Cr17Ni12Mo2), NiTi alloy (nominal composition: Ni55.8Ti), L605 cobalt alloy (nominal composition: Co20Cr15W10Ni) and MP35N cobalt alloy (nominal composition: Co35Ni20Cr10Mo). However, these alloys contain Cr and Ni elements. Although they exist as metal compounds and are protected by surface passivation protective films, these metals still have the risk of ion precipitation of harmful elements after being implanted in the human body. Long-term evaluation of the corrosion resistance and biocompatibility of these materials in the human body environment is required. Finding a metal material for coronary stents to solve the risk of harmful element ion precipitation in existing metal materials has become a research frontier in materials science and medicine. Summary of the invention

[0003] The above-mentioned commonly used coronary stent metal materials have the problem of harmful elements. The present invention provides a processing method for a TiMn medical titanium alloy coronary drug-coated stent to solve the problem of harmful metal ion precipitation caused by corrosive media after implantation into the human body, which damages the health of the patient.

[0004] In order to solve the above technical problems, the present invention specifically provides the following technical solutions.

[0005] A medical titanium alloy coronary artery drug-coated stent. The titanium alloy gold Kirschner wire wire comprises the following chemical components by mass percentage: Mn 5.0% to 14.0%, Fe≤0.30%, O≤0.16%, N≤0.01%, H≤0.001%, and the balance is Ti.

[0006] The present invention uses a vacuum consumable arc furnace to melt alloy ingots, and then forging and hot rolling to obtain titanium alloy rods, and then mechanical perforation, peeling, centerless grinding, cold rolling, cold drawing and straightening to obtain the final titanium alloy capillary, and finally the finished metal stent is prepared through microsecond fiber laser engraving, vacuum heat treatment and electrochemical polishing. Then, polylactic acid-glycolic acid copolymer (PLGA) and rapamycin are mixed into a solution in proportion, and the drug solution is evenly sprayed on the outer surface of the metal stent by a sprayer, dried in a clean environment, and finally the balloon is transported to the appropriate position of the stent by a special crimping machine to prepare a titanium alloy coronary artery drug-coated stent.

[0007] A method for processing a medical titanium alloy coronary artery drug-eluting stent specifically comprises the following steps:

[0008] Step 1: preparing a titanium alloy ingot by vacuum consumable smelting;

[0009] Step 2: Forging with a fast forging machine and a precision forging machine;

[0010] Step 3: hot rolling is performed using a horizontal rolling mill to prepare a rough bar with a suitable size;

[0011] Step 4: After mechanical drilling, a rough tube blank is obtained; the surface roughness is improved by peeling and centerless grinding;

[0012] Step 5: cold rolling is performed by a cold rolling mill, and repeated annealing is performed in the middle to obtain a thin tube billet;

[0013] Step 6: Using a drawing device to draw and deform the tube blank to obtain a capillary tube blank;

[0014] Step 7: Use a slider straightening machine to straighten the wire;

[0015] Step 8: Carve out the coronary stent blank using microsecond fiber laser;

[0016] Step nine, performing vacuum heat treatment on the bracket blank;

[0017] Step 10: electrochemically polishing the stent blank to prepare a finished metal stent;

[0018] Step 11, preparing a drug solution of polylactic acid-co-glycolic acid (PLGA) and rapamycin;

[0019] Step 12: Use a sprayer to evenly spray the drug solution on the outer surface of the metal stent and dry it in a clean environment; use a special crimping machine to transport the balloon to the appropriate position of the stent to prepare a titanium alloy coronary artery drug-coated stent.

[0020] Furthermore, in the step one, it is required to use sponge titanium, metal Mn, metal Fe, and compound TiO2, and mix the materials according to the titanium alloy composition, and adopt vacuum self-consumable three-time smelting. Argon is filled during the smelting process. The argon filling pressure is 5000~10000Pa during the first smelting, and the argon filling pressure is 20000~30000Pa during the second and third smeltings to obtain TiMn titanium alloy ingots.

[0021] Furthermore, in the step 2, it is required to carry out blank forging at 1000°C to 1100°C, and carry out finish forging at 800°C to 950°C, the holding time is controlled at 1 to 6 hours, and the deformation amount of each fire is not less than 60%.

[0022] Furthermore, in the step three, the rolling temperature is controlled to be 750-850° C., the holding time is 1-2 hours, and the deformation amount of each pass is controlled within 15%.

[0023] Furthermore, in the step 4, the rolled bar is first machined into a suitable length, and then the rolled billet is prepared into a TiMn alloy tube by a precision drilling process, and the inner surface roughness Ra is controlled within 1.6 μm; the outer surface roughness Ra of the tube is controlled within 1.6 μm by peeling and centerless grinding.

[0024] Furthermore, in the step 5, the tube blank is subjected to multiple cold rolling deformations on a cold rolling tube mill, and the deformation amount of a single pass is controlled at 10-25%, followed by intermediate vacuum annealing treatment, and then continued cold rolling, and finally a fine-sized TiMn alloy tube blank is prepared.

[0025] Furthermore, in step six, a multi-pass cold drawing deformation is performed on the thin tube blank on a drawing machine, and the deformation amount of a single pass is controlled at 10-20%, followed by an intermediate vacuum annealing treatment, and then continued cold drawing, and finally a TiMn alloy capillary tube blank is prepared.

[0026] Furthermore, in step seven, a straightening machine is used to straighten the capillary tube, and it is necessary to ensure that the curvature is less than 0.3 mm / m.

[0027] Furthermore, in step eight, the long capillary is first processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 10-30 μs, a laser power of 100-300 W, and a pulse frequency of 8000-15000 Hz.

[0028] Furthermore, in the step nine, the coronary artery blank is subjected to vacuum heat treatment at a temperature of 600-700°C for 5-15 minutes, and then rapidly cooled by liquid nitrogen before being taken out of the furnace, in order to eliminate the internal stress formed in the stent blank during laser engraving and further adjust the mechanical properties of the stent.

[0029] Furthermore, in the step ten, the stent blank is electrochemically polished, the polishing liquid is 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, the voltage is 10~20V, the temperature is -20~-30℃, and the roughness Ra value of the inner and outer surfaces is less than 0.1μm, thereby preparing a finished titanium alloy stent.

[0030] Furthermore, in the step eleven, PLGA is dissolved in ethyl acetate or tetrahydrofuran and stirred thoroughly, and then an appropriate amount of rapamycin is added and further stirred thoroughly to form a uniform solution, ensuring that the drug loading in the finished stent coating is 2 to 3 μg / mm 2 .

[0031] Furthermore, in step 12, the metal stent is placed in a sleeve, fixed on an automatic ultrasonic spraying device, and then ultrasonic atomization spraying is performed, the spraying pressure is 0.2~0.28 MPa, the atomization power is 1.2~2.0 W, the liquid feeding rate is 0.1~0.2mL / min, and the coating thickness is 5~6 μm; after spraying, it is dried in a clean environment and then vacuum dried for 24~48h. The balloon is transported to the appropriate position of the stent using a special crimping machine to prepare a titanium alloy coronary artery drug-eluting stent.

[0032] The design concept of the present invention is:

[0033] The composition design of the alloy of the present invention includes, by mass percentage, 5.8% to 6.2% Al element, 3.8% to 4.2% V element, 0.15% to 0.2% Fe element, 0.08% to 0.13% O element, ≤0.05% C element, ≤0.005% H element, ≤0.01% N element, and the balance is Ti. The design idea of ​​the above composition is to improve the strength of titanium by adding the Mn element necessary for the human body to form a medical titanium alloy, completely eliminate the risk of human body damage caused by the precipitation of harmful elements, and meet the requirements of the coronary artery drug-eluting stent for the performance of raw materials.

[0034] The present invention adopts a special processing technology, adopts a vacuum consumable arc furnace to melt an alloy ingot, and then after forging and hot rolling and other processes, by controlling the heating temperature and deformation during hot processing, the strength and grain size of the alloy can be effectively controlled, and a reasonable match between strength and plasticity can be achieved to obtain a titanium alloy rod, and then through mechanical perforation, peeling, centerless grinding, cold rolling, cold drawing and straightening, the strength and plasticity of the alloy can be effectively controlled by the deformation amount of cold rolling and drawing and the intermediate annealing temperature, so as to obtain the final finished titanium alloy capillary; finally, the stent structure is finely engraved by a microsecond fiber laser to achieve precise forming of the stent; the inner and outer surface roughness of the stent is effectively reduced by high-precision machining and electrochemical polishing, so as to prepare a qualified coronary artery metal stent; by mixing PLGA and rapamycin solution, and spraying the solution on the metal stent by an ultrasonic atomizing sprayer, and drying, a titanium alloy coronary artery drug-coated stent is prepared.

[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects.

[0036] 1. The present invention provides a method for preparing a medical titanium alloy coronary drug-eluting stent. This method can produce titanium alloy rods, tubes and coronary stents of various specifications, providing alloy raw materials for cardiovascular medical devices.

[0037] 2. The present invention improves the strength of titanium by adding the Mn element necessary for the human body to form a medical titanium alloy, which completely eliminates the risk of human body damage caused by the precipitation of harmful elements and meets the requirements of coronary stents for raw material performance.

[0038] 3. The present invention uses microsecond fiber laser to finely carve the stent structure to achieve precise forming of the stent; through high-precision machining holes and electrochemical polishing, the roughness of the inner and outer surfaces of the stent is effectively reduced, thereby preparing a qualified coronary artery drug-coated stent. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Microstructure of the Φ4.0 mm TiMn alloy tube prepared in Example 1.

[0040] Figure 2 Microstructure of the Φ3.0 mm TiMn alloy tube prepared in Example 2.

[0041] Figure 3 Microstructure of the Φ2.75 mm TiMn alloy tube prepared in Example 3.

[0042] Figure 4 Microstructure of the Φ2.25 mm TiMn alloy tube prepared in Example 4. DETAILED DESCRIPTION

[0043] Some embodiments of the present invention are disclosed below, and those skilled in the art can appropriately improve the process parameters according to the content of this article. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0044] A medical titanium alloy coronary artery drug-coated stent. The titanium alloy gold Kirschner wire wire comprises the following chemical components by mass percentage: Mn 5.0% to 14.0%, Fe≤0.30%, O≤0.16%, N≤0.01%, H≤0.001%, and the balance is Ti.

[0045] A method for processing a medical titanium alloy coronary artery drug-eluting stent specifically comprises the following steps:

[0046] Step 1: preparing a titanium alloy ingot by vacuum consumable smelting;

[0047] Step 2: Forging with a fast forging machine and a precision forging machine;

[0048] Step 3: hot rolling is performed using a horizontal rolling mill to prepare a rough bar with a suitable size;

[0049] Step 4: After mechanical drilling, a rough tube blank is obtained; the surface roughness is improved by peeling and centerless grinding;

[0050] Step 5: cold rolling is performed by a cold rolling mill, and repeated annealing is performed in the middle to obtain a thin tube billet;

[0051] Step 6: Using a drawing device to draw and deform the tube blank to obtain a capillary tube blank;

[0052] Step 7: Use a slider straightening machine to straighten the wire;

[0053] Step 8: Carve out the coronary stent blank using microsecond fiber laser;

[0054] Step nine, performing vacuum heat treatment on the bracket blank;

[0055] Step 10: electrochemically polishing the stent blank to prepare a finished metal stent;

[0056] Step 11, preparing a drug solution of polylactic acid-co-glycolic acid (PLGA) and rapamycin;

[0057] Step 12: Use a sprayer to evenly spray the drug solution on the outer surface of the metal stent and dry it in a clean environment; use a special crimping machine to transport the balloon to the appropriate position of the stent to prepare a titanium alloy coronary artery drug-coated stent.

[0058] Furthermore, in the step one, it is required to use sponge titanium, metal Mn, metal Fe, and compound TiO2, and mix the materials according to the titanium alloy composition, and adopt vacuum self-consumable three-time smelting. Argon is filled during the smelting process. The argon filling pressure is 5000~10000Pa during the first smelting, and the argon filling pressure is 20000~30000Pa during the second and third smeltings to obtain TiMn titanium alloy ingots.

[0059] Furthermore, in the step 2, it is required to carry out blank forging at 1000°C to 1100°C, and carry out finish forging at 800°C to 950°C, the holding time is controlled at 1 to 6 hours, and the deformation amount of each fire is not less than 60%.

[0060] Furthermore, in the step three, the rolling temperature is controlled to be 750-850° C., the holding time is 1-2 hours, and the deformation amount of each pass is controlled within 15%.

[0061] Furthermore, in the step 4, the rolled bar is first machined into a suitable length, and then the rolled billet is prepared into a TiMn alloy tube by a precision drilling process, and the inner surface roughness Ra is controlled within 1.6 μm; the outer surface roughness Ra of the tube is controlled within 1.6 μm by peeling and centerless grinding.

[0062] Furthermore, in the step 5, the tube blank is subjected to multiple cold rolling deformations on a cold rolling tube mill, and the deformation amount of a single pass is controlled at 10-25%, followed by intermediate vacuum annealing treatment, and then continued cold rolling, and finally a fine-sized TiMn alloy tube blank is prepared.

[0063] Furthermore, in step six, a multi-pass cold drawing deformation is performed on the thin tube blank on a drawing machine, and the deformation amount of a single pass is controlled at 10-20%, followed by an intermediate vacuum annealing treatment, and then continued cold drawing, and finally a TiMn alloy capillary tube blank is prepared.

[0064] Furthermore, in step seven, a straightening machine is used to straighten the capillary tube, and it is necessary to ensure that the curvature is less than 0.3 mm / m.

[0065] Furthermore, in step eight, the long capillary is first processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 10-30 μs, a laser power of 100-300 W, and a pulse frequency of 8000-15000 Hz.

[0066] Furthermore, in the step nine, the coronary artery blank is subjected to vacuum heat treatment at a temperature of 600-700°C for 5-15 minutes, and then rapidly cooled by liquid nitrogen before being taken out of the furnace, in order to eliminate the internal stress formed in the stent blank during laser engraving and further adjust the mechanical properties of the stent.

[0067] Furthermore, in the step ten, the stent blank is electrochemically polished, the polishing liquid is 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, the voltage is 10~20V, the temperature is -20~-30℃, and the roughness Ra value of the inner and outer surfaces is less than 0.1μm, thereby preparing a finished titanium alloy stent.

[0068] Furthermore, in the step eleven, PLGA is dissolved in ethyl acetate or tetrahydrofuran and stirred thoroughly, and then an appropriate amount of rapamycin is added and further stirred thoroughly to form a uniform solution, ensuring that the drug loading in the finished stent coating is 2 to 3 μg / mm 2 .

[0069] Furthermore, in step 12, the metal stent is placed in a sleeve, fixed on an automatic ultrasonic spraying device, and then ultrasonic atomization spraying is performed, the spraying pressure is 0.2~0.28 MPa, the atomization power is 1.2~2.0 W, the liquid feeding rate is 0.1~0.2mL / min, and the coating thickness is 5~6 μm; after spraying, it is dried in a clean environment and then vacuum dried for 24~48h. The balloon is transported to the appropriate position of the stent using a special crimping machine to prepare a titanium alloy coronary artery drug-eluting stent.

[0070] Example 1.

[0071] The composition design of the titanium alloy Kirschner wire in this embodiment includes, by mass percentage, 6.04% Mn element, 0.18% Fe element, 0.10% O element, 0.0007% H element, 0.005% N element, and the balance Ti.

[0072] The processing method of the titanium alloy coronary artery drug-eluting stent is as follows:

[0073] Step 1: Use sponge titanium, metal Mn, metal Fe, and compound TiO2, and prepare the materials according to the titanium alloy composition. Use vacuum self-consumable three-time smelting. The argon filling pressure during the first smelting is 7600MPa, the argon filling pressure during the second smelting is 25300Pa, and the argon filling pressure during the third smelting is 28700Pa, so as to obtain a φ365mm titanium alloy ingot with stable and uniform composition.

[0074] Step 2: Forging at 1070°C, finishing at 850°C, holding time at 5h, and deformation at 72% per fire.

[0075] Step 3: Roll the forged rough bar billet using a horizontal rolling mill at a rolling temperature of 800°C for a holding time of 1.5 hours, control the deformation amount of each pass at 15%, and prepare a φ20mm titanium bar billet.

[0076] Step 4: Process the rolled rod into a suitable length, and then use the drilling process to prepare a TiMn alloy tube, and control the inner surface roughness Ra to 1.6μm. The outer surface roughness Ra of the tube is controlled within 1.6μm through peeling and centerless grinding.

[0077] Step 5: cold-roll the rough tube billet on a cold rolling mill, with the deformation of a single pass controlled at 21%. The core rod is made of high-speed steel and lubricated with lubricating oil. After removing the oil, vacuum annealing is performed at 700°C for 1 hour, followed by cold-rolling deformation. This cycle is repeated for multiple passes to finally produce a φ8mm titanium alloy tube billet.

[0078] Step six, cold drawing the titanium alloy tube blank on the drawing equipment, the deformation of a single pass is controlled at 10-18%, the core rod is made of high-speed steel material, and lubricated with lubricating oil; after removing the oil, vacuum annealing is performed at 650°C for 1h, and then cold drawing is performed again. This cycle is repeated for multiple passes to finally prepare a φ4.0mm titanium alloy capillary.

[0079] Step 7: Use a straightening machine to straighten the capillary tube, and the straightness after straightening is less than 0.3 mm / m. The room temperature tensile properties of the capillary tube are shown in Table 1.

[0080] Table 1 Mechanical properties test results of the Φ4.0 mm TiMn alloy pipe prepared in Example 1

[0081]

[0082] Step 8: First, the long capillary is processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 18 μs, a laser power of 193 W, and a pulse frequency of 13200 Hz.

[0083] Step nine: vacuum heat treatment is performed on the coronary stent blank at a temperature of 680° C. for 11 minutes, and the blank is rapidly cooled by liquid nitrogen before being taken out of the furnace.

[0084] Step 10: electrochemically polish the stent blank with a polishing liquid of 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, a voltage of 17V, a temperature of -22°C, and a roughness Ra value of the inner and outer surfaces less than 0.1 μm, thereby preparing a finished titanium alloy stent.

[0085] Step 11: Dissolve PLGA in ethyl acetate and stir thoroughly, then add an appropriate amount of rapamycin and stir further to form a uniform solution to ensure that the drug loading in the finished stent coating is 2.8 μg / mm 2 .

[0086] Step 12: Place the metal stent in the sleeve, fix it on the automatic ultrasonic spraying equipment, and then perform ultrasonic atomization spraying, with a spraying pressure of 0.21MPa, an atomization power of 2.0W, a liquid feed rate of 0.17mL / min, and a coating thickness of 5.9μm; after spraying, dry it in a clean environment, and then vacuum dry it for 46h. Use a special crimping machine to transport the balloon to the appropriate position of the stent, thereby preparing a titanium alloy coronary artery drug-eluting stent.

[0087] Example 2.

[0088] The composition design of the titanium alloy Kirschner wire wire in this embodiment includes, by mass percentage: the composition design of the titanium alloy Kirschner wire wire in this embodiment includes, by mass percentage: 13.4% Mn element, 0.15% Fe element, 0.12% O element, 0.0004% H element, 0.003% N element, and the balance Ti.

[0089] The processing method of the titanium alloy coronary artery drug-eluting stent is as follows:

[0090] Step 1: Use sponge titanium, metal Mn, metal Fe, and compound TiO2, and prepare the materials according to the titanium alloy composition. Use vacuum self-consumable three-time smelting. The argon filling pressure during the first smelting is 9700MPa, the argon filling pressure during the second smelting is 27000Pa, and the argon filling pressure during the third smelting is 29400Pa, so as to obtain a φ365mm titanium alloy ingot with stable and uniform composition.

[0091] Step 2: Forge the blank at 1050°C and perform finish forging at 930°C. The holding time is controlled at 4h and the deformation of each fire is controlled at 75%.

[0092] Step 3: Roll the forged rough bar billet using a horizontal rolling mill at a rolling temperature of 830°C for a holding time of 2 hours, control the deformation amount of each pass at 12%, and prepare a φ16mm titanium bar billet.

[0093] Step 4: Process the rolled rod into a suitable length, and then use the drilling process to prepare a TiMn alloy tube, and control the inner surface roughness Ra to 1.6μm. The outer surface roughness Ra of the tube is controlled within 1.6μm through peeling and centerless grinding.

[0094] Step 5: The rough tube billet is cold rolled on a cold rolling mill, and the deformation amount of a single pass is controlled at 23%. The core rod is made of high-speed steel and lubricated with lubricating oil. After removing the oil, vacuum annealing is performed at 720°C for 1.5 hours, and then cold rolling is performed again. This cycle is repeated for multiple passes to finally produce a φ6mm titanium alloy tube billet.

[0095] Step six, cold drawing the titanium alloy tube blank on the drawing equipment, the deformation amount of a single pass is controlled at 15-20%, the core rod is made of high-speed steel material, and lubricated with lubricating oil; after removing the oil, vacuum annealing is performed at 660°C, the holding time is 0.5h, and then cold drawing is performed again, and this cycle is repeated for multiple passes to finally prepare a φ3.0mm titanium alloy capillary.

[0096] Step 7: Use a straightening machine to straighten the capillary tube, and the straightness after straightening is less than 0.3 mm / m. The room temperature tensile properties of the capillary tube are shown in Table 2.

[0097] Table 2 Mechanical properties test results of the Φ3.0 mm TiMn alloy pipe prepared in Example 2

[0098]

[0099] Step 8: First, the long capillary is processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 26 μs, a laser power of 276 W, and a pulse frequency of 11500 Hz.

[0100] Step nine: vacuum heat treatment is performed on the coronary stent blank at a temperature of 650° C. for 8 minutes, and the blank is rapidly cooled by liquid nitrogen before being taken out of the furnace.

[0101] Step 10: electrochemically polish the stent blank with a polishing liquid of 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, a voltage of 15V, a temperature of -28°C, and a roughness Ra value of the inner and outer surfaces less than 0.1 μm, thereby preparing a finished titanium alloy stent.

[0102] Step 11: Dissolve PLGA in tetrahydrofuran and stir thoroughly, then add an appropriate amount of rapamycin and stir further to form a uniform solution to ensure that the drug loading in the finished stent coating is 2.6 μg / mm 2 .

[0103] Step 12: Place the metal stent in the sleeve, fix it on the automatic ultrasonic spraying equipment, and then perform ultrasonic atomization spraying, with a spraying pressure of 0.25MPa, an atomization power of 1.8W, a liquid feeding rate of 0.16mL / min, and a coating thickness of 5.5μm; after spraying, dry it in a clean environment, and then vacuum dry it for 36h. Use a special crimping machine to transport the balloon to the appropriate position of the stent, thereby preparing a titanium alloy coronary artery drug-eluting stent.

[0104] Example 3.

[0105] The composition design of the titanium alloy Kirschner wire in this embodiment includes, by mass percentage, 8.7% Mn element, 0.11% Fe element, 0.15% O element, 0.0005% H element, 0.006% N element, and the balance Ti.

[0106] The processing method of the titanium alloy coronary artery drug-eluting stent is as follows:

[0107] Step 1: Use sponge titanium, metal Mn, metal Fe, and compound TiO2, and prepare the materials according to the titanium alloy composition. Use vacuum self-consumable three-time smelting. The argon filling pressure during the first smelting is 5800MPa, the argon filling pressure during the second smelting is 22000Pa, and the argon filling pressure during the third smelting is 24900Pa, so as to obtain a φ365mm titanium alloy ingot with stable and uniform composition.

[0108] Step 2: Forging at 1050°C, finishing forging at 820°C, holding time at 3h, and deformation at 78% per fire.

[0109] Step 3: Roll the forged rough bar billet using a horizontal rolling mill at a rolling temperature of 780°C for 1 hour, control the deformation amount of each pass at 15%, and prepare a φ18mm titanium bar billet.

[0110] Step 4: Process the rolled rod into a suitable length, and then use the drilling process to prepare a TiMn alloy tube, and control the inner surface roughness Ra to 1.6μm. The outer surface roughness Ra of the tube is controlled within 1.6μm through peeling and centerless grinding.

[0111] Step 5: The rough tube billet is cold rolled on a cold rolling mill, and the deformation amount of a single pass is controlled at 18%. The core rod is made of high-speed steel and lubricated with lubricating oil. After removing the oil, vacuum annealing is performed at 680°C for 0.6 h, followed by cold rolling. This cycle is repeated for multiple passes to finally produce a φ5.5mm titanium alloy tube billet.

[0112] Step six, cold drawing the titanium alloy tube blank on the drawing equipment, the deformation of a single pass is controlled at 10-17%, the core rod is made of high-speed steel material, and lubricated with lubricating oil; after removing the oil, vacuum annealing is performed at 640°C, the holding time is 0.5h, and then cold drawing is performed again, and this cycle is repeated for multiple passes to finally prepare a φ2.75mm titanium alloy capillary.

[0113] Step 7: Use a straightening machine to straighten the capillary tube, and the straightness after straightening is less than 0.3 mm / m. The room temperature tensile properties of the capillary tube are shown in Table 3.

[0114] Table 3 Mechanical properties test results of the Φ2.75 mm TiMn alloy tube prepared in Example 3

[0115]

[0116] Step 8: First, the long capillary is processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 12 μs, a laser power of 137 W, and a pulse frequency of 9600 Hz.

[0117] Step nine: vacuum heat treatment is performed on the coronary stent blank at a temperature of 650° C. for 6 minutes, and the blank is rapidly cooled by liquid nitrogen before being taken out of the furnace.

[0118] Step 10: electrochemically polish the stent blank with a polishing liquid of 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, a voltage of 12V, a temperature of -27°C, and a roughness Ra value of the inner and outer surfaces less than 0.1 μm, thereby preparing a finished titanium alloy stent.

[0119] Step 11: Dissolve PLGA in ethyl acetate and stir thoroughly, then add an appropriate amount of rapamycin and stir further to form a uniform solution to ensure that the drug loading in the finished stent coating is 2.5 μg / mm 2 .

[0120] Step 12: Place the metal stent in the sleeve, fix it on the automatic ultrasonic spraying equipment, and then perform ultrasonic atomization spraying, with a spraying pressure of 0.29MPa, an atomization power of 1.4W, a liquid feeding rate of 0.14mL / min, and a coating thickness of 5.4μm; after spraying, dry it in a clean environment, and then vacuum dry it for 32h. Use a special crimping machine to transport the balloon to the appropriate position of the stent, thereby preparing a titanium alloy coronary artery drug-eluting stent.

[0121] Example 4.

[0122] The composition design of the titanium alloy Kirschner wire in this embodiment includes, by mass percentage, 11.3% Mn element, 0.16% Fe element, 0.095% O element, 0.0004% H element, 0.008% N element, and the balance Ti.

[0123] The processing method of the titanium alloy coronary artery drug-eluting stent is as follows:

[0124] Step 1: Use sponge titanium, metal Mn, metal Fe, and compound TiO2, and prepare the materials according to the titanium alloy composition. Use vacuum self-consumable three-time smelting. The argon filling pressure during the first smelting is 8300MPa, the argon filling pressure during the second smelting is 26800Pa, and the argon filling pressure during the third smelting is 29200Pa, so as to obtain a φ365mm titanium alloy ingot with stable and uniform composition.

[0125] Step 2: Forging at 1020°C, finishing at 820°C, holding time at 2h, and deformation at 65% per fire.

[0126] Step 3: Roll the forged rough bar billet using a horizontal rolling mill at a rolling temperature of 760°C for a holding time of 2 hours, control the deformation amount of each pass at 15%, and prepare a φ14mm titanium bar billet.

[0127] Step 4: Process the rolled rod into a suitable length, and then use the drilling process to prepare a TiMn alloy tube, and control the inner surface roughness Ra to 1.6μm. The outer surface roughness Ra of the tube is controlled within 1.6μm through peeling and centerless grinding.

[0128] Step 5: The rough tube billet is cold rolled on a cold rolling mill, and the deformation amount of a single pass is controlled at 13%. The core rod is made of high-speed steel and lubricated with lubricating oil. After removing the oil, vacuum annealing is performed at 640°C for 0.8h, and then cold rolling is performed again. This cycle is repeated for multiple passes to finally produce a φ6mm titanium alloy tube billet.

[0129] Step six, cold drawing the titanium alloy tube blank on the drawing equipment, the deformation amount of a single pass is controlled at 12-20%, the core rod is made of high-speed steel material, and lubricated with lubricating oil; after removing the oil, vacuum annealing is performed at 600°C, the holding time is 0.6h, and then cold drawing is performed again, and this cycle is repeated for multiple passes to finally prepare a φ2.25mm titanium alloy capillary.

[0130] Step 7: Use a straightening machine to straighten the capillary tube, and the straightness after straightening is less than 0.3 mm / m. The room temperature tensile properties of the capillary tube are shown in Table 4.

[0131] Table 4 Mechanical properties test results of the Φ2.25 mm TiMn alloy pipe prepared in Example 4

[0132]

[0133] Step 8: First, the long capillary is processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 12 μs, a laser power of 129 W, and a pulse frequency of 11500 Hz.

[0134] Step nine: vacuum heat treatment is performed on the coronary stent blank at a temperature of 620° C. for 15 minutes, and the blank is rapidly cooled by liquid nitrogen before being taken out of the furnace.

[0135] Step 10: electrochemically polish the stent blank with a polishing liquid of 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, a voltage of 15V, a temperature of -25°C, and a roughness Ra value of the inner and outer surfaces less than 0.1 μm, thereby preparing a finished titanium alloy stent.

[0136] Step 11: Dissolve PLGA in tetrahydrofuran and stir thoroughly, then add an appropriate amount of rapamycin and stir further to form a uniform solution to ensure that the drug loading in the finished stent coating is 2.2 μg / mm 2 .

[0137] Step 12: Place the metal stent in the sleeve, fix it on the automatic ultrasonic spraying equipment, and then perform ultrasonic atomization spraying, with a spraying pressure of 0.23 MPa, an atomization power of 1.6W, a liquid feed rate of 0.11 mL / min, and a coating thickness of 5.2 μm; after spraying, dry it in a clean environment, and then vacuum dry it for 25 hours. Use a special crimping machine to transport the balloon to the appropriate position of the stent, thereby preparing a titanium alloy coronary artery drug-eluting stent.

[0138] The results of the embodiment show that the present invention proposes a method for processing a medical titanium alloy coronary artery drug-eluting stent, wherein an alloy ingot is melted in a vacuum consumable arc furnace, and then after forging and hot rolling and other processes, the strength and grain size of the alloy can be effectively controlled by controlling the heating temperature and deformation during hot working, and a reasonable match between strength and plasticity is achieved to obtain a titanium alloy rod, and then mechanical perforation, peeling, centerless grinding, rolling, drawing and straightening are performed, and the strength and plasticity of the alloy can be effectively controlled by the deformation amount of cold rolling and drawing and the intermediate annealing temperature, thereby obtaining a final product titanium alloy capillary with excellent mechanical properties; the stent structure is finely engraved by a microsecond fiber laser to achieve precise forming of the stent; the inner and outer surface roughness of the stent is effectively reduced by high-precision machining holes and electrochemical polishing, thereby preparing a qualified coronary artery metal stent; the titanium alloy coronary artery drug-eluting stent is prepared by mixing PLGA and rapamycin solution, and spraying the solution on the metal stent by an ultrasonic atomizing sprayer, and drying.

Claims

1. A method for processing a medical titanium alloy coronary artery drug-eluting stent, characterized in that: The titanium alloy Kirschner wire includes the following chemical compositions by mass percentage: Mn 5.0% to 14.0%, Fe≤0.30%, O≤0.16%, N≤0.01%, H≤0.001%, and the balance is Ti; The method comprises the following steps: Step 1: Use sponge titanium, metal Mn, metal Fe, and compound TiO2, and prepare materials according to the titanium alloy composition, and use vacuum self-consumable three-time smelting, and fill argon gas during the smelting process. The argon filling pressure is 5000-10000Pa during the first smelting, and the argon filling pressure is 20000-30000Pa during the second and third smeltings to obtain TiMn titanium alloy ingots; Step 2: Forging with a fast forging machine and a precision forging machine; Step 3: hot rolling is performed using a horizontal rolling mill, the rolling temperature is controlled to be 750-850°C, the holding time is 1-2 hours, the deformation amount of each pass is controlled within 15%, and a rough bar blank with a suitable size is prepared; Step 4: After mechanical drilling, a rough tube blank is obtained; the surface roughness is improved by peeling and centerless grinding; Step 5: cold rolling is performed by a cold rolling mill, and repeated annealing is performed in the middle to obtain a thin tube billet; Step 6: Using a drawing device to draw and deform the tube blank to obtain a capillary tube blank; Step 7: Use a slider straightening machine to straighten the wire, and the curvature is less than 0.3mm / m; Step 8: Carve out the coronary stent blank using microsecond fiber laser; Step nine, performing vacuum heat treatment on the bracket blank; Step 10: electrochemically polishing the stent blank to prepare a finished metal stent; Step 11, preparing a drug solution of polylactic acid-co-glycolic acid (PLGA) and rapamycin; Step 12: Use a sprayer to evenly spray the drug solution on the outer surface of the metal stent and dry it in a clean environment; use a special crimping machine to transport the balloon to the appropriate position of the stent to prepare a titanium alloy coronary artery drug-coated stent.

2. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step 2, it is required to carry out blank forging at 1000℃~1100℃, and fine forging at 800℃~950℃, the holding time is controlled at 1~6h, and the deformation amount of each fire is not less than 60%.

3. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step 4, the rolled bar is first machined into a suitable length, and then the rolled billet is prepared into a TiMn alloy tube by a precision drilling process, and the inner surface roughness Ra is controlled within 1.6 μm; the outer surface roughness Ra of the tube is controlled within 1.6 μm by peeling and centerless grinding.

4. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step 5, the tube blank is subjected to multiple cold rolling deformations on a cold rolling tube mill, and the deformation amount of a single pass is controlled at 10-25%. Then, an intermediate vacuum annealing treatment is performed, and then cold rolling is continued to finally prepare a fine-sized TiMn alloy tube blank.

5. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step six, a multi-pass cold drawing deformation is performed on the thin tube blank on a drawing machine, and the deformation amount of a single pass is controlled at 10-20%. Then, an intermediate vacuum annealing treatment is performed, and then cold drawing is continued to finally prepare a TiMn alloy capillary tube blank.

6. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step eight, the long capillary is first processed into the required length of the coronary stent, and then the coronary stent blank is engraved using a microsecond fiber laser with a pulse width of 10-30 μs, a laser power of 100-300 W, and a pulse frequency of 8000-15000 Hz.

7. The method for processing a medical titanium alloy coronary drug-eluting stent according to claim 1, wherein in step nine, the coronary artery blank is subjected to vacuum heat treatment at a temperature of 600-700° C. for 5-15 minutes, and is then rapidly cooled by liquid nitrogen before being taken out of the furnace.

8. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, wherein in step 10, the stent blank is electrochemically polished, the polishing liquid is 6 vol.% perchloric acid + 35 vol.% n-butanol + 59 vol.% methanol, the voltage is 10~20V, the temperature is -20~-30°C, and the roughness Ra value of the inner and outer surfaces is less than 0.1μm, thereby preparing a finished titanium alloy stent.

9. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step 11, PLGA is dissolved in ethyl acetate or tetrahydrofuran and stirred thoroughly, and then an appropriate amount of rapamycin is added and further stirred thoroughly to form a uniform solution, ensuring that the drug loading in the finished stent coating is 2 to 3 μg / mm 2 .

10. The method for processing a medical titanium alloy coronary artery drug-eluting stent according to claim 1, characterized in that: In step 12, the metal stent is placed in a sleeve and fixed on an automatic ultrasonic spraying device, followed by ultrasonic atomization spraying, with a spraying pressure of 0.2-0.28 MPa, an atomization power of 1.2-2.0 W, a liquid feeding rate of 0.1-0.2 mL / min, and a coating thickness of 5-6 μm; After spraying, dry it in a clean environment and then vacuum dry it for 24 to 48 hours; use a special crimping machine to transport the balloon to the appropriate position of the stent, thereby preparing a titanium alloy coronary artery drug-coated stent.

Citation Information

Patent Citations

  • Manufacturing method of cobalt / iron composite tube for coronary stent and auxiliary equipment

    CN103286155A

  • A low-cost manufacturing method for a large-aperture thick-wall seamless tube made of titanium and an alloy thereof

    CN106493187A

Cited By

  • Degradable zinc alloy intravascular stent

    CN121971209A